KARAKTERISTIK PENDERITA TUBERKULOSIS PARU ANAK YANG RAWAT INAP DI RUMAH SAKIT UMUM DAERAH KOTA PADANGSIDIMPUAN TAHUN 2012 CHARACTERISTICS OF PULMONARY TUBERCULOSIS PATIENTS WHO WERE HOSPITALIZED IN GENERAL HOSPITAL PADANGSIDIMPUAN CITY IN 2012 - veni hardianti; Hiswani .; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Pulmonary tuberculosis (TB) is a infection disease of pulmonary chronic caused by Mycobacterium tuberculosis. In 2011, number of case pulmonary TB in the age group 0-14 years 1727 cases in Indonesia, North Sumatera province there were 104 cases. In 2010 in Medan city there were 194 children who suffer from TB. In 2011, there were 1580 Padangsidimpuan City children who suffer from TB. To determine the characteristics of pulmonary tuberculosis patients who were hospitalized in RSUD Padangsidimpuan city in 2012, conducted a research with case series design and statistical analysis with Chi-Square, Exact Fisher, t-independent and Anova test. Population was 115 patients data with samples all of population (total sampling). Based on sosiodemographic, the highest population is in the age group of 0-4 years old (57.4%), male (53.0%), Islam (87.8%), came from outer Padangsidimpuan City (51.3%), primary pulmonary TB (97.4%), had history of pulmonary TB in the family (60.0%), maintainability long on average 4.64 days, not alone cost (60.0%), recover (90.4%). There was no significant difference between the sexes based on the natural history of disease (p=0.600), there was no significant difference between the average long care based on natural history of disease (p=0.990), there was no significant difference between the average long care based on costs source (p=0.137), there was no significant difference between the average long care based on while come back of home (p=0.528). For parents to give BCG immunization as soon as the child was born because there were many TB case in children and more respon to complaints and symptoms of pulmonary TB in children. To family members who suffer from pulmonary TB as soon as checked up and complete their treatment regularly until 6 months. Keywords : Child Pulmonary Tuberculosis, Characteristics